Delay Mitigation in Tall Building Projects - Muizz Oladapo Sanni-Anibire,; Rosli Mohamad Zin,; Olusanya Olatunji (Aadam), (2022)
The rise of tall buildings in urban centres across the globe has been attributed to the need to create more urban space for an imminent population explosion and urbanization crisis. Despite the potential of this building typology as a sustainable alternative to urban design, it has become notorious for being delayed, and sometimes abandoned. The research domain is saturated with numerous studies on the causes of construction delays, however inadequate effort has been channelled towards the development of prescriptive tools with the potential to mitigate construction delay. The desired solution is one that would employ innovative methods to arrive at problem solving strategies for the ultimate purpose of delay mitigation. Today, the fourth industrial revolution (IR 4.0) offers the construction industry a unique opportunity to solve its many woes, such as delays, through leveraging the capabilities of digital technologies such as artificial intelligence and machine learning. Thus, it is the purpose of this book to describe a delay mitigation framework proposed for tall building projects based on the application of machine learning. The application of machine learning is considered in three major areas of project delay risk mitigation including “reliable cost estimates”, “reliable duration estimates”, and “delay risk assessment”. Interestingly, the concept of the delay mitigation framework can be extended to other project types, besides tall building projects.